Refleksi Undang-Undang Nomor 17 Tahun 2003 Tentang Keuangan Negara - Kamaroesid, Herry (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2015)
The law No. 17 year 2003 concerning State Finance is the first law in the state finance adopted since Indonesia's independence. This writing is aimed at analyzing how far the law has been successful in managing the state budget for the las 10 (ten) years. Library is used in this method. Based on the research it can be concluded study with the adoption of Law No. 17 Year 2003 concerning state budget management has not yet shown satisfactory result